Cultivating creativity: the relationship between inclusive leadership, psychological safety, vitality, openness to experience and creative work involvement - Mavrokordatos, Amanda (Stellenbosch : Stellenbosch University, 2015)
Thesis (MCom)--Stellenbosch University, 2015